Thermochemical energy: development of battery prototypes and storage materials - Desage, Lucie (Curtin University, 2024)
Thermochemical energy storage is particularly relevant for power production facilities and can be used to run heat-to-power engines. This research established the challenges of integrating thermochemical energy storage materials into a battery setup. The development of the storage materials, including metal carbonates and metal hydrides, encompassed the study of the physical properties of the materials, and the assessment of their cycling performance to integrate large-scale thermochemical batteries.